Integrated Animal Health Care Using Iot - Katemboh et al., Emi Mwaka (International Journal of Advanced Science and Technology, 2020)
The aim of this research was to design an Integrated Animal Health Care System using IoT. The methodology employed was the use of various sensors to obtain the physical and environmental data of the animals and their surroundings. The type of data obtained was temperature, heart rate and air quality. With the data obtained, there is a control system also implemented to control the effects of the data obtained by the sensors and some of the controlling methods employed include the use of a massaging unit to lower the animal heart rate, fans to cool the animals environment and a window that can be opened and closed depending on the air quality. The sensor data is then transmitted from a LoRa Node to a LoRa Gateway and eventually passed to a Node-Red cloud server for storing. The data from the server is then passed to an IoT dashboard for viewing as well as to a mobile application. This research has attained social sustainability as there is environmental health monitoring of factors such as humidity, temperature as well monitoring of the quality of air produced. Economic sustainability was also achieved as this research helps to monitor and control animal health which in turn helps owners to reduce on the costs they would have incurred in constantly having to take their animals to veterinary doctors for checkups.